Electromotive Force and Measurement in Several Systems - Kara, Sadik (IntechOpen, 2011)
This book is devoted to different sides of Electromotive Force theory and its applications in Engineering science and Industry. The covered topics include the Quantum Theory of Thermoelectric Power (Seebeck Coefficient), Electromotive forces in solar energy and photocatalysis (photo electromotive forces), Electromotive Force in Electrochemical Modification of Mudstone, The EMF method with solid-state electrolyte in the thermodynamic investigation of ternary copper and silver chalcogenides, Electromotive Force Measurements and Thermodynamic Modelling of Electrolyte in Mixed Solvents, Application of Electromotive Force Measurement in Nuclear Systems Using Lead Alloys, Electromotive Force Measurements in High-Temperature Systems and finally, Resonance Analysis of Induced EMF on Coils.